2021
DOI: 10.1111/1365-2435.13856
|View full text |Cite
|
Sign up to set email alerts
|

Tree species mixing causes a shift in fine‐root soil exploitation strategies across European forests

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 107 publications
(209 reference statements)
0
6
0
Order By: Relevance
“…This fundamental divergence implies contrasting influences of mycorrhizal type on root economics. For example, while a trade‐off between mycorrhizal colonization intensity and mean root diameter has been clearly established for AM species, such evidence is scarce for ECM species (Kong et al ., 2014; Bergmann et al ., 2020; Wambsganss et al ., 2021). As such, it has been hypothesized instead that a higher branching intensity (BI, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…This fundamental divergence implies contrasting influences of mycorrhizal type on root economics. For example, while a trade‐off between mycorrhizal colonization intensity and mean root diameter has been clearly established for AM species, such evidence is scarce for ECM species (Kong et al ., 2014; Bergmann et al ., 2020; Wambsganss et al ., 2021). As such, it has been hypothesized instead that a higher branching intensity (BI, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, growth of a seedling that has regenerated below an established canopy of larger trees will be restricted by shading and below-ground competition of the bigger trees; its subsequent performance will then be influenced by this as well as by its shade tolerance characteristics. There are numerous studies of intra-and inter-specific interactions in these more complex forests (Biging and Dobbertin 1995;Vettenranta 1999;Uriarte et al 2004a,b;Canham et al 2004Canham et al , 2006Dolezal et al 2009;Forrester et al 2011;del Rió et al 2016;Quiñonez-Barraza et al 2018;Zambrano et al 2019Zambrano et al , 2020Bongers 2020;Trogisch et al 2021;Wambsganss et al 2021;Bi et al 2022). That of Coates et al (2009) for mixed hardwood and softwood species of British Columbia, Canada, suggested that below-ground competitive processes tended to be appreciably more important in affecting growth than did above ground shading effects (their Fig.…”
Section: Discussionmentioning
confidence: 97%
“…For example, a recent study in a controlled biodiversity experiment suggests that the increased diversity effects on productivity over time may attribute to the increased dominance of arbuscular mycorrhizae trees in species mixture (Deng et al, 2023). When productivity increases with time and diversity, plant communities likely adjust their nutrient acquisition strategies via root morphology plasticity or mycorrhizal colonization (Wambsganss, Freschet, et al, 2021). Since a trade‐off exists between carbon investment in root growth and mycorrhizal symbiosis (Bergmann et al, 2020), we speculate that the observed positive mixture effect on fine root length may to some extent related to the effects of mycorrhizal colonization.…”
Section: Discussionmentioning
confidence: 99%